UnAustralian art ten essays on transnational art history - Butler, Rex 19XX- (Power Publications/University of Sydney, 2022)
UnAustralian Art: Ten Essays on Transnational Art History proposes a radical rethinking of Australian art. Rex Butler and ADS Donaldson do not seek to identify a distinctive national sensibility; instead, they demonstrate that Australian art and artists have always been engaged in struggles and creative exchanges with the rest of the world. Examining Australian art as much from the outside in as the inside out, Butler and Donaldson's methodology opens Australian art history to an encyclopedic multitude of hitherto excluded stories from Australian expatriates who lived and worked overseas to artists who came from elsewhere and continued to make art in Australia. Beginning with the impressionist John Russell at the turn of the century in France and ending with the great Anmatyerre artist Emily Kame Kngwarreye in the late twentieth century, the book presents new research detailing the artistic connections between Australia and New Zealand, France, Britain, Germany, Asia, North America, South America, and the Pacific. This book asks us to reconsider who an Australian artist is and has been. In a world of increasing global connectedness, this new history of UnAustralian art is a history of the present, helping us understand the Australia of the twenty-first century
Keywords: Art, Australian / 20th century; Art, Australian / History; Nationalism and art / History; Art, Australian; Art australien; Art australien / Histoire; Nationalisme et art / Histoire; History; Essays